2016
DOI: 10.4103/0971-3026.184418
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted imaging in extracranial head and neck schwannomas: A distinctive appearance

Abstract: Purpose:To evaluate the diffusion weighted (DW) magnetic resonance imaging (MRI) features of the extracranial schwannomas of head and neck.Materials and Methods:The MRI (including DWI) of 12 patients with pathologically proven head and neck schwannomas (4 men, 8 women, with mean age of 32.6 years; age range 16–50 years) were retrospectively evaluated. Images were analyzed for signal intensity and morphology on conventional sequences followed by the qualitative evaluation of DW images (DWI) and measurement of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This study suggested that the ADC quantitative assessment could not provide significant value for the differential diagnosis of both of the tumours. We found that the mean ADC values of these tumours were greater than the mean ADC values of neck paragangliomas and schwannomas [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study suggested that the ADC quantitative assessment could not provide significant value for the differential diagnosis of both of the tumours. We found that the mean ADC values of these tumours were greater than the mean ADC values of neck paragangliomas and schwannomas [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we observed that 13 cases had obviously higher signal intensity than that of the spleen in T2WI. The DWI of 13 cases represents the first report of cases in which the high signal intensity is much higher than that of the spleen, and the mean ADC values of all tumors were greater than those of neck paragangliomas 16 , 17 . DWI assessment may, therefore, be of significant value for differential diagnosis.…”
Section: Discussionmentioning
confidence: 93%
“… 5 The heterogeneous appearance of schwannomas may be attributed to degeneration and the plethora of cellular components such as cystic and xanthomatous lesions. 7 Small schwannomas tend to have homogenous contrast enhancement after gadolinium administration, whereas larger lesions have more heterogeneous enhancement. 5 FDG uptake by schwannomas is variable, so it is difficult to differentiate between benign and malignant tumours.…”
Section: Discussionmentioning
confidence: 99%